CHiME-6 Challenge: Tackling Multispeaker Speech Recognition for Unsegmented Recordings - Watanabe, Shinji; Mandel, Michael; Barker, Jon; Vincent, Emmanuel; Arora, Ashish; Chang, Xuankai; Khudanpur, Sanjeev; Manohar, Vimal; Povey, Daniel; Raj, Desh; Snyder, David; Subramanian, Aswin Shanmugam; et al. (arXiv:2004.09249, 2020)
Following the success of the 1st, 2nd, 3rd, 4th and 5th CHiME challenges we organize the 6th CHiME Speech Separation and Recognition Challenge (CHiME-6). The new challenge revisits the previous CHiME-5 challenge and further considers the problem of distant multi-microphone conversational speech diarization and recognition in everyday home environments. Speech material is the same as the previous CHiME-5 recordings except for accurate array synchronization. The material was elicited using a dinner party scenario with efforts taken to capture data that is representative of natural conversational speech. This paper provides a baseline description of the CHiME-6 challenge for both segmented multispeaker speech recognition (Track 1) and unsegmented multispeaker speech recognition (Track 2). Of note, Track 2 is the first challenge activity in the community to tackle an unsegmented multispeaker speech recognition scenario with a complete set of reproducible open source baselines providing speech enhancement, speaker diarization, and speech recognition modules.